STUDENTS’ PERCEPTION ON THE USE OF INTERNET APPLICATIONS IN SUBMITTING ASSIGNMENTS AT THE FOURTH SEMESTER OF FKIP UKI TORAJA - Viktor Siumarlata (Journal of Language Testing and Assessment, 2021)
The objective of this research is to know about the students’ perceptions of the use of the Internet for application purposes in submitting assignments in the fourth semester of the English Department at FKIP UKI. In this research, the writer used the qualitative method. The instrument of this research is a semistructured interview. The subjects of this research were the fourth-semester students of the English Department of FKIP UKI for the academic year 2017/2018. I used the accidental sampling technique with seven students as my subjects.The results show that internet applications make it easier for students to submit assignments more quickly and can send assignments wherever they are. Some of them say that internet applications as a medium are very helpful in the teaching and learning process. They have a positive perception because the use of internet applications facilitates and also saves time. There is no need to waste time; students are required to be more modern; there is no need to waste paper; and students do not fail science and technology. Some of them, when using internet applications, have problems, like when they do not have data, do not have Android, or when the network is damaged